2019
DOI: 10.1186/s13677-019-0144-9
|View full text |Cite
|
Sign up to set email alerts
|

A Neuro-fuzzy approach for user behaviour classification and prediction

Abstract: Big data and cloud computing technology appeared on the scene as new trends due to the rapid growth of social media usage over the last decade. Big data represent the immense volume of complex data that show more details about behaviours, activities, and events that occur around the world. As a result, big data analytics needs to access diverse types of resources within a decreased response time to produce accurate and stable business experimentation that could help make brilliant decisions for organizations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Thus, the OSNs provide an unprecedented amount of data, reflecting the behavior of the users [7] . However, analyzing the behavior of the users in an OSN is a complex task [8] , and thus, some models to detect anomalies in the user behavior have been studied [9] . Some studies have focused particularly on the domain of user behavior analysis on social media for instance in the contexts of political events [10] , [11] , a diverse range of recommendation systems [12] [14] , public health [2] , [15] , communication network recommendations [16] , and prediction of urban traffic trends [12] , [17] , among others.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the OSNs provide an unprecedented amount of data, reflecting the behavior of the users [7] . However, analyzing the behavior of the users in an OSN is a complex task [8] , and thus, some models to detect anomalies in the user behavior have been studied [9] . Some studies have focused particularly on the domain of user behavior analysis on social media for instance in the contexts of political events [10] , [11] , a diverse range of recommendation systems [12] [14] , public health [2] , [15] , communication network recommendations [16] , and prediction of urban traffic trends [12] , [17] , among others.…”
Section: Introductionmentioning
confidence: 99%
“…Data mining technology can screen useful tournament information in a large amount of data so that fans can easily understand the team's tactics and combinations through edited data, which is more conducive to discussion and analysis. e results of basketball matches are uncertain, and the usual in uences include subjective and objective factors [35]. ese factors, such as the weather at that time, the altitude of the venue, climate, and so on, may also be due to the athlete's character, mood, interpersonal relationship, and so on.…”
Section: Time Index Rotation Angle Indexmentioning
confidence: 99%
“…They found that LSTM showed highest accuracy. Atta-ur-Rahman et al [11] proposed a neuro-fuzzy approach for supervised learning of user behaviour prediction. They used temporal logs of user's interaction with web site as dataset and found that their approach performed well.…”
Section: IImentioning
confidence: 99%